Dendrimeric calcium-sensitive MRI probes: the first low-field relaxometric study. Issue 5 (13th January 2020) - Garello, Francesca; Gündüz, Serhat; Vibhute, Sandip; Angelovski, Goran; Terreno, Enzo
Abstract : In the present work the first investigation ever of calcium sensitive dendrimer relaxation mechanisms at low fields is reported. Abstract : Different classes of small- or nano-sized calcium-sensitive probes for magnetic resonance imaging (MRI) have been proposed in the last two decades. These compounds have been developed mainly for functional MRI purposes and tested in vivo in different animal models. Most of them are paramagnetic systems that change their relaxivity in the presence of the divalent ion calcium, resulting in increased T 1 or T 2 contrast. In this work, we report the investigation of their relaxometric behavior at low magnetic fields, specifically the comparison of the monomeric Ca-sensitive probe and the corresponding dendrimer conjugates of generations 0, 1 and 2 (G0, G1 and G2, respectively). As a result, a relaxivity hump between 10 and 100 MHz of the Larmor frequency progressively appeared with an increase in the size of the investigated contrast agent, indicative of a restricted rotational motion of the complexes as long as the size of the molecule increases. The same trend with a more pronounced effect was detectable in the presence of calcium. The relaxivity enhancement for the Ca 2+ adducts, primarily caused by an increase of the hydration state of Gd 3+, went from ca. 130% for the monomeric probe to ca. 310% for the G2 dendrimer conjugate at 0.5 T and 25 °C. T 1 weighted magnetic resonance images acquired at 1 T displayed the strong ability of these systems to change their contrast according to the presence of calcium at this field, thus laying the basis for promising future in vivo applications.